Adequacy of thermal ambience in silk production sheds with different toppings - Salgdo, Douglas D'Alessandro [UNESP]; MacLean, Priscilla Ayleen Bustos [UNESP]; Pereira, Danilo Florentino [UNESP]; De Oliveira Neto, Paulo [UNESP] (American Society of Agricultural and Biological Engineers (ASABE), 2016)
At every stage of life of the Bombyx mori there is a great temperature (between 20 and 28°C) and favorable humidity (greater than 70%) to their physiological development. This paper proposed analytical method for evaluating the adequacy of thermal variables with respect to the recommendations identified in the scientific literature for three buildings with different types of coverage: ceramic (CB), zinc (ZB) and zinc with white paint (ZBW). Thermal ambience variables monitored for 23 days (2015, May, in Bastos - Brazil), were the air temperature (AT) and relative humidity (RH) and calculated the radiant heat load (RHL). The assessment of each variable was performed by means of an analytical study of graphics with the number of daily medium records and minimum, maximum reference lines (dotted line) representing the limits recommended specification, when found. For all variables were found inadequate records obtained compared to the recommended specifications for the three types of shed coverage, with the following characteristics of non-compliance: downward trend, depending on weather conditions external to all variables; for AT was included still great variability to present average results out of specification limits. For RH, were no found upper limits, which it is assumed that can harm production when very high. Thus, the purpose of evaluating the adequacy proved effective to verify the non-compliance of important variables of the internal environment. There is a need to be deployed an air conditioning system so that the appropriate conditions are met thermal ambience.
Keywords: Animal welfare; Coverage; Data analysis; Production efficiency; Thermal environment